2021
DOI: 10.35892/jimpk.v1i1.495
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Pelaksanaan Keselamatan Pasien (Pasien Safety) Di Rumah Sakit Umum Daerah Labuang Baji Makassar

Abstract: Keselamatan pasien (patient sefety) merupakan suatu variabel untuk mengukur dan mengevaluasi kualitas pelayanan keperawatan yang berdampak terhadap pelayanan kesehatan. Tujuan penelitian ini ialah untuk mengevaluasi pelaksanaan keselamatan pasien di ruang inap Rumah Sakit Umum Daerah Labuang Baji Makassar. Jenis penelitian yang digunakan ialah metode deskriktif kuantitatif dengan tehnik observasional. Metode sampling yang digunakan dengan tehnik purposive sampling didapatkan sampel 70 responden sesuai dengan k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
0
0
3
Order By: Relevance
“…The results of bivariate analysis, which showed that there was a significant relationship with the behavior of nurses in carrying out documentation of nursing care were knowledge, workload, nursing SOPs. This research is in line with (Haritsa & Haskas, 2021)8 evaluation of the implementation of patient safety (patient safety) at the public hospital in the Labuang baji area, Makassar. The results of the study obtained on the implementation of patient safety showed that drug safety had been implemented quite well, it was known that from 70 respondents, 66 respondents (94.3%) had done drug safety is good, while those who do not practice drug safety are 4 respondents (5.7%).…”
Section: Bivariate Analysissupporting
confidence: 72%
“…The results of bivariate analysis, which showed that there was a significant relationship with the behavior of nurses in carrying out documentation of nursing care were knowledge, workload, nursing SOPs. This research is in line with (Haritsa & Haskas, 2021)8 evaluation of the implementation of patient safety (patient safety) at the public hospital in the Labuang baji area, Makassar. The results of the study obtained on the implementation of patient safety showed that drug safety had been implemented quite well, it was known that from 70 respondents, 66 respondents (94.3%) had done drug safety is good, while those who do not practice drug safety are 4 respondents (5.7%).…”
Section: Bivariate Analysissupporting
confidence: 72%
“…Merokok sangat besar peranannya meningkatkan tekanan darah, hal ini disebabkan oleh nikotin yang terdapat di dalam rokok yang memicu hormon adrenalin yang menyebabkan tekanan darah meningkat (Sangka, Basri, & Hanis, 2021;Tanjung, Meilianingsih, Suheti, T., & Husni, 2021). Nikotin diserap oleh pembuluh-pembuluh darah di dalam paru dan diedarkan ke seluruh aliran darah lainnya sehingga terjadi penyempitan pembuluh darah.…”
Section: Pembahasanunclassified
“…Data yang ditemukan yaitu Bali 1,4%, Sulawesi Selatan 0,69%, Aceh 0,68%, Jawa Barat 2,8%, Jawa Timur 11,7%, Sumatera Selatan 6,9%, Yogyakarta 13,8%, Jawa Tengah 15,9%, DKI Jakarta 37,9%. Data yang ditemukan di Indonesia analisa insiden yang terjadi dilingkungan rumah sakit belum sepenuhnya berkembang, sehingga ada pembatasan kejadian yang terjadi pada pasien yang menjamin keselamatan pasien (Haritsa & Haskas, 2021).…”
Section: Latar Belakangunclassified